PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS SCRATCH DALAM PEMBELAJARAN IPAS KELAS IV SD NEGERI KARANGSARI - Rachmawaty, Rima; Nana Sutarna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Development of Scratch-Based Audio-Visual Learning Media for IPAS Learning in Grade IV of Karangsari Elementary School Primary School Teacher Education Study Program, 2025. The purpose of this research is to develop audio-visual learning media based on the Scratch application for IPAS (Science, Social Studies, and Natural Science) learning in Grade IV, to determine the feasibility of the Scratch-based audio-visual learning media, and to find out the effectiveness of the learning media by observing whether there is an increase in student learning outcomes after using the Scratch-based audio-visual learning media. The research was conducted in Grade IV of Karangsari Elementary School with a sample of 20 students. The research design used the Borg and Gall research and development procedure as modified by Prof. Dr. Nana Syaodih Sukmadinata, who proposed three main stages in research and development: (1) Preliminary Study, which includes a literature review and a field study; (2) Model Development, which includes drafting the initial model, a limited trial, a wider trial, and the final model product; and (3) Effectiveness Test, which includes a pretest, treatment, posttest, and the final model. The research results show that the feasibility of this learning media received a percentage of 95% from the material expert with a